2023
DOI: 10.3390/ijerph20054624
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gut Microbiota and Multiple Sclerosis: A Systematic Review

Abstract: Introduction: Multiple sclerosis (MS) is a chronic inflammatory neurodegenerative disease mediated by autoimmune reactions against myelin proteins and gangliosides in the grey and white matter of the brain and spinal cord. It is considered one of the most common neurological diseases of non-traumatic origin in young people, especially in women. Recent studies point to a possible association between MS and gut microbiota. Intestinal dysbiosis has been observed, as well as an alteration of short-chain fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 114 publications
1
9
0
Order By: Relevance
“…The controversy over the abundance of Blautia , Dorea , Faecalibacterium, Methanobrevibacter, Parabacteroides , and Ruminococcaceae in MS and HC groups is consistent with the findings of a systematic review and review, probably due to significant differences in disease severity and duration, as well as differences in changes in gut microbiota ( Ordoñez-Rodriguez et al, 2023 ).…”
Section: A Link Between Ms and Gut Microbiotasupporting
confidence: 70%
“…The controversy over the abundance of Blautia , Dorea , Faecalibacterium, Methanobrevibacter, Parabacteroides , and Ruminococcaceae in MS and HC groups is consistent with the findings of a systematic review and review, probably due to significant differences in disease severity and duration, as well as differences in changes in gut microbiota ( Ordoñez-Rodriguez et al, 2023 ).…”
Section: A Link Between Ms and Gut Microbiotasupporting
confidence: 70%
“…Based on the MR study results, the hypothesis that the association may be established through short-chain fatty acids was proIn the gut microbiota, Clostridium butyricum is considered a signi cant bene cial bacterium. Research has made it clear that its protective effect against in ammatory diseases is very important, especially those associated with in ammation, such as in ammatory bowel disease, periodontitis, and chronic in ammatory diseases associated with neurodegenerative diseases [34][35][36] . Butyricoccus is an important producer of butyrate, which is a mainstay of the family of short-chain fatty acids and can effectively resist in ammations by regulating in ammatory responses through a variety of pathways [37] .…”
Section: Discussionmentioning
confidence: 99%
“…The other detrimental effects caused by the dysbiosis are disruption in the energy metabolism, increased cell death, and modulation of immune response, which contributes to the advancement of various diseases ( Noble et al, 2017 ), adding to the pathogenic mechanisms of several disorders, including neurodegeneration ( Mulak and Bonaz, 2015 ). Dysbiosis has been linked to several other diseases, including: (a) Inflammatory Bowel Disease (IBD): dysbiosis in the GM gut microbiome is associated with IBD, and other gut related disorder like Crohn’s disease and ulcerative colitis ( Di Martino et al, 2023 ); (b) Irritable Bowel Syndrome (IBS): it is associated with dysbiosis, which is characterized by abdominal pain and altered bowel habits ( Körner and Lorentz, 2023 ); (c) Obesity: GM is associated with obesity and has been linked with the dysbiosis due to increased body weight and fat accumulation ( Zhang et al, 2023 ); (d) Type 2 diabetes (T2DM): various studies have demonstrated correlation of T2DM with dysbiosis and stated that may dysbiosis is a contributing factor to T2DM ( He et al, 2023 ); (e) Allergies and Asthma: dysbiosis in the gut and respiratory microbiome has been associated with an increased risk of allergies and asthma ( Kleniewska and Pawliczak, 2023 ); (f) Mental Health disorders: dysbiosis in the gut microbiome has been linked to mental health disorders, including depression, anxiety, and autism ( Młynarska et al, 2022 ); (g) Autoimmune Diseases: dysbiosis in the GM is correlated with autoimmune diseases, including rheumatoid arthritis (RA) and multiple sclerosis (MS; Ordoñez-Rodriguez et al, 2023 ). In addition, variation in the diversity of GM is associated with aging and aging gut demonstrated a decrease in the microbial diversity ( Cheng et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%